Lewis Acid Guests in a P8W48 Archetypal Polyoxotungstate Host: Enhanced Proton Conductivity via Metal‐Oxo Cluster within Cluster Assemblies. (30th July 2018) - Yang, Peng; Alsufyani, Maryam; Emwas, Abdul‐Hamid; Chen, Chaoqin; Khashab, Niveen M.
Abstract: Complexes made by hosts that completely surround their guests provide a means to stabilize reactive chemical intermediates, transfer biologically active cargo to a diseased cell, and construct molecular‐scale devices. By the virtue of inorganic host–guest self‐assembly, nucleation processes in the cavity of a P8 W48 ‐archetype phosphotungstate has afforded a nanoscale 16‐Al III ‐32‐oxo cluster and its Ga III analogue that contain the largest number of Al III /Ga III ions yet found in polyoxometalate (POM) chemistry. Interestingly, the rich Lewis acid Al III centers within the Lewis base POM support shows an exceptional proton conductivity of 4.5×10 −2 S cm −1 (85 °C, 70 % RH; RH: relative humidity), which is by far the highest conductivity reported among POM‐based single‐crystal proton conductors. Abstract : Saure Gäste : Die Wirt‐Gast‐Assemblierung des radförmigen P8 W48 ‐Phosphowolframats mit stark Lewis‐sauren Zentren führt zu Polyoxometallaten (POMs) mit den bisher größten Al III ‐ und Ga III ‐Oxoclustern. Die erhöhte Protonenleitfähigkeit der Al III ‐Derivate wird durch den synergistischen Effekt der reichhaltigen Lewis‐Säure/Base‐Paare mit den sauren Nitratfunktionen hervorgerufen.